Validation of a Farsi version of the Early Childhood Oral Health Impact Scale (F-ECOHIS) - Jafarzadeh Mehdi; IJadi Mohammad H; Golkari Ali; Jabarifar Seyed-Ebrahim; Khadem Parvin (BMC, 2010)
Abstract Background The Early Childhood Oral Health Impact Scale (ECOHIS) has recently been developed to assess oral health-related quality of life (OHRQoL) of pre-school children in English speaking communities. This study aimed to translate the ECOHIS into Farsi and test its psychometric properties for use on 2- to 5-year-old children of Farsi speaking Iranian families. Methods EHOHIS questionnaire was translated into Farsi using a standardized forward-backward linguistic translation method. Its face and content validity was tested in two small pilot studies. In the main study, a convenience sample of 260 parents of 2- to 5-year-old children in Isfahan and Tehran were invited to complete the final Farsi version of the ECOHIS (F-ECOHIS) and answer two global self-rating questions about their children's dental appearance and oral health. Association between F-ECOHIS scores and answers to the two self-rating questions, and the correlation between child (9 items) and family (4 items) sections of the F-ECOHIS were used to assess the concurrent and convergent validity of the questionnaire. Internal consistency reliability of the F-ECOHIS was tested using Cronbach's alpha coefficient test and item total and inter-item correlations. One third of participants were invited to complete the F-ECOHIS again after 2 weeks to evaluate the test-retest reliability of the questionnaire. Results Two hundred and forty six parents were included in the main study. The association between the F-ECOHIS scores and the two self-rating questions and the correlation between its child and family sections were significant (P < 0.001). Cronbach's alpha coefficient of the F-ECOHIS and its child and family sections were 0.93, 0.89, and 0.85 respectively. Coefficients did not increase by deleting any item. The corrected item total correlation coefficient ranged from 0.52 to 0.74. The inter-item correlation coefficient ranged between 0.30 and 0.73. Seventy three parents participated in the follow up study for re-testing the questionnaire. Comparison of their test and re-test scores had a weighted kappa of 0.81 and inter-class correlation (ICC) of 0.82. Conclusion The F-ECOHIS questionnaire was valid and reliable for assessing the OHRQoL of 2- to 5-year-old pre-school children of Farsi speaking parents.